Life-threatening bronchopulmonary dysplasia: a British Paediatric Surveillance Unit Study. Issue 1 (28th June 2021) - Naples, Rebecca; Ramaiah, Sridhar; Rankin, Judith; Berrington, Janet; Harigopal, Sundeep
Abstract : Objectives: To assess the minimum incidence of life-threatening bronchopulmonary dysplasia (BPD), defined as need for positive pressure respiratory support or pulmonary vasodilators at 38 weeks corrected gestational age (CGA), in infants born <32 weeks gestation in the UK and Ireland; and to describe patient characteristics, management and outcomes to 1 year. Methods: Prospective national surveillance study performed via the British Paediatric Surveillance Unit from June 2017 to July 2018. Data were collected in a series of three questionnaires from notification to 1 year of age. Results: 153 notifications met the case definition, giving a minimum incidence of 13.9 (95% CI: 11.8 to 16.3) per 1000 live births <32 weeks' gestation. Median gestation was 26.1 (IQR 24.6–28) weeks, and birth weight 730 g (IQR 620–910 g). More affected infants were male (95 of 153, 62%; p<0.05). Detailed management and outcome data were provided for 94 infants. Fifteen died at median age 159 days (IQR 105–182) or 49.6 weeks CGA (IQR 43–53). Median age last receiving invasive ventilation was 50 days (IQR 22–98) and total duration of pressure support for surviving infants 103 (IQR 87–134) days. Fifty-seven (60.6%) received postnatal steroids and 22 (23.4%) pulmonary vasodilators. Death (16%) and/or major neurodevelopmental impairment (37.3%) or long-term ventilation (23.4%) were significantly associated with need for invasive ventilation near term and pulmonary hypertension. Conclusions: This definition of life-threatening BPD identified an extremely high-risk subgroup, associated with serious morbidity and mortality. Wide variability in management was demonstrated, and future prospective study, particularly in key areas of postnatal steroid use and pulmonary hypertension management, is required.